Perancangan Sistem Informasi Pencatatan Data Laporan Vaksinasi Berbasis Web Menggunakan Metode Waterfall (Studi kasus di Dinas Kesehatan Kota Bandung) - Agus Deka Pujawan; Raihan Abiyu Rendra; Jaenal Arifin; Cahyadi Agustin (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Abstract Currently, the field vaccination data reporting activities held by health care facilities (Fasyankes) in collaboration with Bandung Health Office are still done manually, it results in the process of recording vaccination report data takes a lot of time so that it becomes inefficient and also vulnurable to the accumulation of patient data or data redudancy at the time of input of vaccine patient data and it makes the process of activities recording becomes ineffective. The purpose of this study is to create a report data recording information system that can make it easier for vaccination officers to faciliate the input of patient data has been vaccine and make reports of patient data has been vaccine and make reports of patient data has been vaccine with the provosion of a print feature of the report as well as the final results of accurate data information. The system is built using PHP programming language, Bootsrap UI and MySQL Database also use Waterfall Method by Roger S.Pressman which this method helps the author in creating system design, design, testing and system implementation. The result of this study is the creation of Web-Based Information System Data Report use Waterfall Method that can be used directly by the health care facility vaccination officer (Fasyankes) do together with the vaccination officer from the bandung health office at the time of field activities. Keywords: Data Reports, Software Engineering, Vaccine Covid-19.